Caspase-Mediated Cleavage of Human Cortactin during Influenza A Virus Infection Occurs in Its Actin-Binding Domains and Is Associated with Released Virus Titres - Chen, Da-Yuan; Husain, Matloob (Viruses, 2020)
Influenza A virus (IAV) exploits host factors to multiply and cause disease. An in-depth knowledge of this interaction of IAV with the host will aid the development of anti-IAV intervention strategies. Previously, we demonstrated that host cortactin, an actin filament-binding protein promotes IAV infection, but undergoes degradation via a lysosome-associated apoptotic pathway during the late stages of IAV infection. Next, we wanted to further understand the mechanisms and significance of this phenomenon. By using the RNA interference screens and site-directed mutagenesis followed by western blotting, we found that lysosome protease, cathepsin C is involved in cortactin degradation in human cells infected with IAV. Furthermore, executioner apoptotic caspase, caspase-3 not caspase-6 or caspase-7 is involved in cortactin degradation during IAV infection, and caspase-3 cleavage site is located in the first actin-binding repeat of cortactin polypeptide. Finally, when expressed ectopically, the cleavage-resistant cortactin mutants decreased the amount of IAV progeny released from infected cells that was enhanced by the cleavage-sensitive cortactin wild type. These data strengthen the hypothesis proposed earlier that host cortactin plays an inhibitory role during the late stages of IAV infection, and IAV is facilitating its degradation to undermine such function.